Socioeconomic, dietary, nutrition, body weight and epidemiologic transitions: three nations at different stage of development - Linando, Arzelia Yorika; Lee, Soo-Kyung (Progress in Nutrition, 2018)
Objectives: The present study examined how socio-economic changes has associated with changes of dietary, nutritional, physical activity, body weight and diseases based on the systems of transition. This study empirically examined the system of transitions using data from three nations (Indonesia, Korea, and the US) at different stage of development. This study expanded the previous study by 1) replicating with more recent data, 2) including three nations for comparison, and 3) including diseases as a variable in addition to the other transitions. Methods: Indicators of socio-economic (GDP and urban population percentage), dietary (consumption of rice, sugar & sweeteners, vegetable oil, animal fat, milk, and meat), nutrition (consumption of energy, protein and fat), physical activity (proportion of population engaged in different employment sectors), body weight (overweight and obesity percentages), and epidemiological (communicable and non-communicable disease rates) transitions were collected from international open sources: the World Bank, FAO databank, WHO Global Health Observatory data repository, and from a publication issued by National Statistics Bureaus. Eight different years starting from 1980 to 2015, with a five-year interval between years, were examined. Spearman’s rank correlation and path analysis was conducted using SPSS and SAS. Results: While GDP increased in all three nations, proportion of urban population significantly increased only in Indonesia. Regarding dietary transition, only vegetable oil consumption significantly increased in all three nations, but no particular significant trends were found in nutrition transition. All three nation showed significant decrease in percentage of the population employed in agriculture and significant increase in percentage of the population in service sector. Body weight transition was significantly occurred in all three nations. Only fasting glucose level significantly increased in all three nations, while high blood pressure and total blood cholesterol level fluctuated over the study period and by sex. The model of the system of transitions showed that epidemiological transition was highly related to body weight transition, which, in turn, significantly affected by physical activity and dietary transition. Conclusions: This study found that the three nations at different stage of development showed different level in each transition and that the transitions were interrelated as shown in the system of transitions. This systematic view would be helpful to find ways to solve current nutrition and health problems.